Study of Production Performance of Layers in Different Types of Cages with Different Stocking Densities - Mangnale, G. A.; Desai, D. N.; Ranade, A. S.; Avari, P. E. (International Journal of Livestock Research, 2019)
The production performance of layers reared in different types of cages with different stocking densities was evaluated on 320 layers of BV300 strain for 20 weeks. The birds were divided in eight groups with four replicates of ten birds. Groups A, B and C were housed in California cages with floor space of 450, 465 and 750 cm2 per bird; groups D, E and F were housed in battery cages with floor space of 465, 450 and 750 cm2 per bird; groups G and H were housed in enhanced cages with floor space of 750 and 450 cm2 per bird, respectively. In California cages, the birds allotted with floor space of 750 cm2 per bird recorded significantly better production performance. In battery cages, the birds provided with floor space of 450 cm2 per bird recorded better production performance where as in enhanced cages, the birds reared with floor space of 750 cm2 per bird recorded significantly better production performance. In California and enhanced cages, the broken eggs were lower where lesser floor space was offered to the birds. In battery and enhanced cages, the birds reared with floor space of 450 and 750 cm2 per bird recorded higher net profit. It was concluded that, with respect to the performance of layers in the different cages studied in the experiment, the enhanced cage system with floor space of 750 cm2 per bird was found to be better.